Antimicrobial sesquiterpenoids from Laurencia obtusa Lamouroux - Bawakid Nahed O.; Alarif Walied M.; Alorfi Hajer S.; Al-Footy Khalid O.; Alburae Najla A.; Ghandourah Mohamed A.; Al-Lihaibi Sultan S.; Abdul-hameed Zainab H. (Open Chemistry, 2017)
Purification of the organic extract of Laurencia obtusa Lamouroux by column chromatography and preparative thin layer chromatography provided four new compounds: a eudesmane-type sesquiterpenoid [eudesma-4(15),11-diene-5,7-diol (1)], a cuparane-type sesquiterpenoid [10-hydroxycuparaldehyde (2)], and two nor-cuparanes [3-hydroxy-15-nor-cuparan-10β-ol (3) and 2-bromo-3-hydroxy-15-nor-cuparan-10β-ol (4)]. Structural identification was made possible by comparison of spectral data with those reported in the literature. Compounds 3 and 4 are significant as nor-cuparanes are rarely isolated from marine environment. 1 showed moderate anticandidal activity, whereas 2 exhibited reasonable antibacterial activity against multidrug-resistant bacteria (especially Gram-positive). All the compounds are nontoxic to Artemia salina.